Summer rainfall dissolved organic carbon, solute, and sediment fluxes in a small Arctic coastal catchment on Herschel Island (Yukon Territory, Canada) - Coch, Caroline; Lamoureux, Scott F.; Knoblauch, Christian; Eischeid, Isabell; Fritz, Michael; Obu, Jaroslav; Lantuit, Hugues (Arctic Science, 2018)
Coastal ecosystems in the Arctic are affected by climate change. As summer rainfall frequency and intensity are projected to increase in the future, more organic matter, nutrients and sediment could be mobilized and transported into the coastal nearshore zones. However, knowledge of current processes and future changes is limited. We investigated streamflow dynamics and the impacts of summer rainfall on lateral fluxes in a small coastal catchment on Herschel Island in the western Canadian Arctic. For the summer monitoring periods of 2014–2016, mean dissolved organic matter flux over 17 days amounted to 82.7 ± 30.7 kg km −2 and mean total dissolved solids flux to 5252 ± 1224 kg km −2 . Flux of suspended sediment was 7245 kg km −2 in 2015, and 369 kg km −2 in 2016. We found that 2.0% of suspended sediment was composed of particulate organic carbon. Data and hysteresis analysis suggest a limited supply of sediments; their interannual variability is most likely caused by short-lived localized disturbances. In contrast, our results imply that dissolved organic carbon is widely available throughout the catchment and exhibits positive linear relationship with runoff. We hypothesize that increased projected rainfall in the future will result in a similar increase of dissolved organic carbon fluxes.